Harmonizing Technology and Nature: A review of Green AI role in Sustainable Technology and Environmental Protection - S.mohammed, Ghada; basil gazi, Osama; a mahdi, Walaa (Journal of Madenat Alelem University College, 2024)
This study explores the dynamic landscape of Green Artificial Intelligence(Green AI), focusing on the latest trends and future prospects shaping the field of sustainable technology. The convergence of artificial intelligence (AI) and environmental consciousness is evident in several key areas. Beginning with energy-efficient model architectures, researchers are actively developing innovative approaches to maintain high-performance standards while minimizing computational and energy demands during both training and inference processes, as well as Quantum computing’s potential to address complex optimization challenges related to sustainability. The integration of AI in climate change modelling has become increasingly prevalent, demonstrating its capacity to advance our understanding of environmental challenges. Concurrently, efforts to optimize the integration of renewable energy sources into power grids using AI algorithms continue to gain traction, with a focus on improving energy forecasting, distribution, and management. Sustainable data centre design remains a pivotal area of exploration, with innovations aimed at maximizing energy efficiency, incorporating renewable energy sources, and implementing resource-efficient hardware. The study also highlights the growing importance of ethical considerations in Green AI, addressing issues related to fairness, transparency, and environmental justice to ensure responsible development and deployment. Lastly, the anticipation of policies and regulations surrounding Green AI underscores the increasing global focus on accountability and environmental responsibility. This comprehensive exploration of Green AI trends not only reflects the current state of the field but also provides insights into the future of sustainable technology, where AI and environmental consciousness coalesce to shape a more eco-friendly and responsible future.